GAME PENGENALAN ORGAN TUBUH MANUSIA BERBASIS MULTIMEDIA MENGGUNAKAN STRUKTUR ALUR MULTIMEDIA HIERARKI - Hamdan Hamdan; Umar Mansyuri; Beni Junedi (Universitas Bina Bangsa, 2021)
Natural science is the study of nature and all its contents in it, one of which studies the human body organs which are divided into two parts, namely internal organs and human external organs. The delivery of learning materials in schools is still conventional, namely using the media of printed books. The delivery media that is still conventional and many terms on the material of human organs cause students to have difficulty in understanding the material. There are many media that can be applied in learning human organs, one of which is by using learning game media. Game is a medium of delivery that is widely enjoyed by all people. So it is necessary to create an application system or multimedia-based learning game, as a solution to solving the problem of students' difficulties in understanding the material. Multimedia has aspects that are of interest to students because of its appearance in the form of images, animations, audio, and video. In designing this game, the human body uses a hierarchical multimedia flow structure, while the software used to build this game is Adobe Photoshop, Adobe Flash, and CorelDraw. The results of the game design will be implemented into a multimedia-based human organ recognition game using a multimedia hierarchy structure which is expected to be an effective way of delivering material in overcoming various problems that occur in learning human organs